ETHNO-BOTANICAL SURVEY OF IRVINGIA GABONENSIS AND IRVINGIA WOMBOLU IN SELECTED MARKETS IN AKINYELE LOCAL GOVERNMENT AREA, OYO STATE, NIGERIA - Odeyale, Olajumoke (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigated the ethnobotanical uses, market availability, and challenges associated with Irvingia gabonensis and Irvingia wombolu in selected markets within Akinyele Local Government Area, Oyo State, Nigeria. Data were collected from 80 respondents, comprising herbal practitioners and herb sellers, through structured questionnaires and interviews and analyzed using descriptive statistics. Results revealed that 57.5% of respondents were male, with the majority aged between 51 and 60 years, while 76.25% were married. Awareness of the species was generally high, with most respondents sourcing them from forests and marketing different plant parts such as seeds, bark, leaves, and fruits, predominantly during the rainy season. The plants were reported to possess strong medicinal value, with 96.3% of respondents affirming their therapeutic effectiveness in treating ailments such as fever, dysentery, and stomach disorders. Preservation methods largely relied on sun and air drying. Major challenges faced by respondents included high transportation costs (95%), inadequate capital (85%), poor road networks (82.5%), deforestation (75%), and seasonal scarcity (61.25%). Suggested solutions included reduction of transport costs, afforestation programs, and improved road infrastructure. The study underscores the socio-economic and medicinal importance of Irvingia species while highlighting the need for sustainable utilization and conservation strategies to ensure their long-term availability.